The influence of environmental factors on phytoplankton composition and dynamics along the Johor Strait using conventional and metabarcoding approaches - Mohd. Din, Monaliza (2021)
Johor Strait is a narrow strait located between Malaysia and Singapore; and serves as the main marine aquaculture area for the two countries. The Strait was subjected to anthropogenic activities that led to eutrophication and an increase in harmful algae blooms (HAB). However, the information associated with spatial-temporal bloom dynamic, and the environmental constraints affecting the phenology of the harmful phytoplankton species in the Johor Strait is still lacking. Hence, a field study was conducted from January 2017 to September 2019 as an effort to continuously monitor the water quality and occurrence of HAB in the Strait. Phytoplankton and water samples were collected monthly during high tide along the Johor Strait and in situ physical and chemical parameters such as temperature, salinity, pH, dissolved oxygen, nitrate-nitrogen (NO3-N), ammonia-nitrogen (NH3-N), nitrite-nitrogen (NO2-N), silicate-silica (SiO3-Si), phosphate-phosphorus (PO4-P) and chlorophyll a were determined. The phytoplankton compositions were identified microscopically. A metabarcoding approach targeting the 18S ribosomal RNA (rRNA) gene marker has also been employed to study the spatial-temporal structure of HAB community assemblages between May 2018 and September 2019, covering 19 stations across the Johor Strait. In this study, a total of 48 genera of phytoplankton were identified morphologically. The most diverse group was diatom (32 genera) followed by the dinoflagellate (15 genera). Bloom-forming diatoms included Chaetoceros, Coscinodiscus, Eucampia, Guirnadia, Navicula, Pseudo-nitzschia, Rhizosolenia, Skeletonema and Thallasiosira; and dinoflagellate Blixaea quinquecornis and Scrippsiella were succeeded by predominantly single species or co-dominated by more than a single species throughout the study period. Nitrate and silicate were found to be the triggering factor for the bloom-forming of diatoms, while phosphate was important for sustaining dinoflagellates succession in the Strait. An attempt has been made to determine the cause of hypoxia-anoxia condition in the inner part of Johor Strait, suggesting that high chlorophyll-a concentration (up to 48.8 μg/L) and high biomass blooms of Skeletonema, Chaetoceros, Rhizosolenia, and Thalassiosira observed at the inner part of the strait to be the main cause. A hypoxic to anoxic dead zone, with the dissolved oxygen levels ranging from 0.19 to 1.7 mg/L, was identified in the inner Johor Strait, covering an estimated area of 10.3 km2. The occurrence of high biomass diatom blooms has likely induced the formation of the hypoxic-anoxic zone along the inner part of Johor Strait. The operational taxonomic units (OTUs) of HAB taxa retrieved from the metabarcoding datasets revealed a much higher number of taxa (26 OTUs) than before, with 12 new taxa identified. The most common and abundant HAB taxa in the strait (frequency of occurrences >70%) are Heterosigma akashiwo, Fibrocapsa japonica, Pseudo-nitzschia pungens, Dinophysis spp., Gymnodinium catenatum, Alexandrium leei, and Alexandrium tamiyavanichii. This study illustrated that the nutrient dynamic influenced by environmental variables were the key factor in the succession of the phytoplankton community and HAB assemblages in the tropical eutrophic of Johor Strait.